The Relationship Between Democracy, Media Independence and Citizen Journalism with the Press in the Jokowi Era - Restendy, Mochammad Sinung; Noorhaidi Hasan; Rama Kertamukti (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This study examines the relationship between democracy, media independence, and citizen journalism during Joko Widodo’s administration. Within the media ecosystem, the press plays a crucial role as an information provider, a social control mechanism, and the fourth pillar of democracy. However, during Jokowi’s presidency, the independence of mainstream media has faced significant challenges. This study identifies that mainstream media in Indonesia have experienced a distortion of independence due to political intervention, media ownership affiliations with those in power, and various regulations that suppress press freedom. This study employs a qualitative approach using Critical Discourse Analysis, allowing data collection from multiple sources, including mainstream media, social media platforms, as well as legal and academic documents. The findings show that democracy and press independence have declined during Jokowi's era. Although citizen journalism provides a new space for freedom of expression, challenges remain in the form of legal threats, political intervention, and difficulties in maintaining information credibility. Therefore, further efforts are required to strengthen press freedom, including regulatory reforms and the enhancement of an independent media ecosystem, to ensure that democracy in Indonesia can develop more robustly. The strategy of diversifying income to reduce dependence on capital owners, government advertising, or conglomerates with political interests is the ideal theory and practice to be offered to the press in the future.